Analysis of Indonesian Government Policies in Response to the Covid-19 Pandemic-Induced Mass Layoffs - Rahmad Agus Dwianto; Arief Bakhtiar Darmawan; Suswanta Suswanta; Muchamad Zaenuri; Elpeni Fitrah (Jurnal Public Policy, 2023)
This study intends to evaluate Indonesian government strategies for dealing with the Covid-19 pandemic's high rate of mass layoffs. The labor market has been significantly impacted by the Covid-19 outbreak. This study employs a qualitative methodology, gathering a range of information and relevant sources. Information regarding Indonesian government policies, issues with layoffs and the law there, as well as the country's economic status in light of the COVID-19 pandemic, acquired from literary studies, journals, and other relevant sources. In this essay, the author separates the data into three categories: the instances of layoffs in Indonesia during the Covid-19 outbreak; government policy to address the issue; and implementation of government policy to address the issue. The analysis discovered that the Indonesian government has put repressive and preventive measures in place. Preventative measures, such as offering incentives and lowering working hours and worker compensation, to avoid layoffs. Repressive measures were also put in place to lessen the effects of termination of employment under the pre-employment card program. Although the pre-employment program would be more effective if the training were conducted on-site at the training center, it is less effective because it is conducted online. Programs to manage workforce, enhance quality, and ensure legal protection must be strengthened by the government. The workforce, the government, and business actors must all participate in a complete bottom-top strategy.